St. Kitts and Nevis : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 2000)
The sugar industry has contracted severely in 1998 and 1999, by 21 percent and 18 percent, respectively, principally owing to hurricane damage in both years. The sugar industry has continued to perform poorly as the St. Kitts Sugar Manufacturing Corporation (SSMC), the sole producer and exporter of sugar, continued to take heavy losses. The government is currently considering various options for dealing with the problems facing the industry and has initiated a public consultation to seek the views of the populace, using a summary of a World Bank-funded study on the costs and benefits as background.